Description of two new HLA alleles, A*01:128 and C*05:88, identified in Spanish individuals. Issue 2 (14th June 2013) - Sánchez‐Gordo, F.; Balas, A.; Gomez‐Zumaquero, J. L.; Prat, I.; Vicario, J. L.
Abstract : Two novels alleles, HLA‐A*01:128 and HLA‐C*05:88 are characterized.